Diffusion‐tensor MRI and tractography of the esophageal wall ex vivo. Issue 3 (31st October 2013) - Yamada, Ichiro; Hikishima, Keigo; Miyasaka, Naoyuki; Tokairin, Yutaka; Kawano, Tatsuyuki; Ito, Eisaku; Kobayashi, Daisuke; Eishi, Yoshinobu; Okano, Hideyuki; Shibuya, Hitoshi
<x xml:space="preserve">Abstract</x> Purpose To demonstrate the feasibility of diffusion‐tensor magnetic resonance imaging (MRI) and tractography as a means of evaluating the individual layers of the normal esophageal wall by using esophageal specimens containing carcinoma. Materials and Methods Twelve esophageal specimens each containing a carcinoma that were preserved in formalin were studied with a 7.0‐T small‐bore MR system equipped with a four‐channel phased‐array surface coil. Diffusion‐tensor MR images were obtained with a field of view of 50–60 × 25–30 mm, matrix of 256 × 128, section thickness of 1 mm, b value of 1000 sec/mm2, and motion‐probing gradient in seven noncollinear directions. The diffusion‐weighted images, apparent diffusion coefficient (ADC) maps, fractional anisotropy (FA) maps, direction‐encoded color FA maps, and tractographic images in the 12 esophageal specimens were compared with the histopathologic findings, which served as the gold standard. Results The diffusion‐weighted images, ADC maps, FA maps, and direction‐encoded color FA maps depicted the normal esophageal wall in all 12 specimens (100%) as consisting of eight layers, which clearly corresponded to the tissue layers of the esophageal wall. The ADC, FA, λ1, λ2, and λ3 values of each layer of the normal esophageal wall were significantly different from the corresponding values of the adjacent layer or layers of the esophageal wall. Diffusion‐tensor tractographic images were able to selectively display the layers of the normal esophageal wall. Conclusion By looking at the normal part of esophageal specimens containing carcinoma, we have demonstrated that diffusion‐tensor MRI and tractography are capable of depicting the individual tissue layers of the normal esophageal wall. J. Magn. Reson. Imaging 2014;40:567–576. © 2013 Wiley Periodicals, Inc.